Pengaruh Kompetensi, Skeptisme Profesional dan Budaya Organisasi terhadap Efektivitas Audit Aparat Inspektorat dengan Independensi sebagai Variabel Moderasi - Ubaidillah, Moh. (JIFA (Journal of Islamic Finance and Accounting), 2018)
This study aims to determine the influence of professional skepticism, competence and organizational culture on the effectiveness of auditing inspectorate apparatus with independence as a moderating variable. This research is a quantitative study of primary data by using questionnaires distributed to the inspectorate. The sample of this research is Madiun Residency with saturation sampling method. The results of this study indicate the competence has a positive effect on the audit of the inspectorate apparatus with the independence as the moderation variable. Professional skepticism has no effect on the effectiveness of the audit of the inspectorate apparatus with independence as a moderating variable. Furthermore, organizational culture negatively affects the effectiveness of the audit of the inspectorate apparatus with independence as a moderating variable. Keywords: Audit Effectiveness, Independence, Competence, Professional Skepticism, Organizational Culture JEL Classification: H 83, M54